Perinatal Mortality In Employed Women - Banerjee Bratati; Chatterjee Pronab; Kanti Dey Tushar (Wolters Kluwer Medknow Publications, 2003)
Research questions: Is employment during pregnancy a risk factor for perinatal mortality? Objective: To study the occurrence of perinatal mortality in working women and compare the results with those of non-working women taken as controls and also between the experience of working women before and after joining service. Study design: Retrospective cohort study. Setting: Jute mills in Hooghly district of West Bengal. Participants: 100 women workers of the mills under study as study population and 100 non-working wives of male workers of the same mills as control population. Statistical analysis: Mortalitz rates, Z test of proportion, x2 test of significance. Results: Stillbirth occurred more often joining service than before (p<0.05) and more in working women in general than controls, but the latter was not statistically significant. Early neonatal death rate was more among controls than the workingwomen and within the latter group, more before joining service than after. On controlling for gravidity and comparing stillbirth in working women after joining service, with controls, it showed high rates in study group till 5th gravida, but only for 1st and 2nd gravida differences were significant (p<0.05). Perinatal mortality also occurred mainly in first 3-4 orders of birth after joining service. Still birth rate in the control group was higher with birth spacing <2years than with spacing>2 years, but in the study group it was lower in case of the former than the latter. Early neonatal death was more in pregnancies with spacing <2 years in both the groups. Conclusion: There is some risk of perinatal loss, especially stillbirth, existing in the working women.